2023
DOI: 10.56536/jebv.v3i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Women Empowerment: A Micro Financing Perspective

Abstract: Women are a massive chunk of Pakistan’s population yet only 25-30 % of women participate in its economic development, and, this low percentage affects overall women empowerment. The current study is an effort to show how governments can enhance women’s empowerment by investing time, money, and resources through micro-financing and skill development for women entrepreneurs and making them a dynamic part of the economy. Current study proposes a Conceptual Three-Dimensional Women Empowerment Model to ensure that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The objective was to examine how functional, social, and psychological factors influence users' intentions to continue using mpayments.In line with the previous studies (Tam et al, 2021;Rezaei & Valaei, 2017;Marinkovic & Kalinic2017), the research found a positive relationship between the expectation of the performance outcomes and the continuity of service use intentions. The specificity and the intangibility of mobile payment services contribute to the fact that the advantages of their use can be perceived only in the process of their use, which raises doubts caused by unfamiliarity and some risks initially, since this new type of service begs another type of payment (Adeel et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The objective was to examine how functional, social, and psychological factors influence users' intentions to continue using mpayments.In line with the previous studies (Tam et al, 2021;Rezaei & Valaei, 2017;Marinkovic & Kalinic2017), the research found a positive relationship between the expectation of the performance outcomes and the continuity of service use intentions. The specificity and the intangibility of mobile payment services contribute to the fact that the advantages of their use can be perceived only in the process of their use, which raises doubts caused by unfamiliarity and some risks initially, since this new type of service begs another type of payment (Adeel et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Studies emphasize the complexity involved in the effectiveness of government empowerment initiatives, highlighting the need for a comprehensive approach (Udayaadithya & Gurtoo, 2014). Governments can enhance women's empowerment through investments in micro-financing, skill development for women entrepreneurs, and integrating them into the economy (Adeel et al, 2023). Efforts to empower women have been undertaken globally to improve their social and health status and involve them in developmental activities (Gupta & Yesudian, 2006).…”
Section: Evaluation Of the Effectiveness Of Government Efforts In Enh...mentioning
confidence: 99%
“…Inclusive economic growth of any country is not possible without women contributing into human capital (Aslam & Shabbir, 2019;Ghouse et al, 2021;Aslam et al, 2021;. Nonetheless, it is obligatory to concede that whilst microfinance harbours substantial potential for facilitating women's empowerment and dropping violence in Pakistan (Adeel et al, 2023), it is not a panacea (Murphy, C., 2018, Shelar, K., 2020Niaz, M. U., & Iqbal, M., 2019). Much of the violence against women is also attributed to their inheritance issues and property rights , combined with their low income or wealth status.…”
Section: Introductionmentioning
confidence: 99%